THE EFFECT OF ALLOPURINOL ON SERUM URIC ACID, BLOOD UREA AND SERUM CREATININE IN CHRONIC KIDNEY DISEASE PATIENTS WITH HIGH URIC ACID - Yousra fathi; Mohammed Hannon Alsodani; Wisam Kadhum H. Alhashemi (Scholar Express Journals, 2022)
Chronic kidney disease is a long-term condition in where the kidneys loss their function lead to several biochemical changes, including the high levels of blood urea, s.creatinine and serum uric acid (hyperuricemia).High uric acid activates the inflammatory response in renal parenchyma leading to renal damage. Allopurinol which is xanthine oxidase enzyme inhibitor is used to lower uric acid concentration. Aim of the study is to study the effect of use of allopurinol on serum level of uric acid, blood urea, serum creatinine in chronic kidney disease patients. Patients and Methods; - A one hundred participant involved , 35 of them were a control group and 65 patients have chronic kidney disease stages 2 to 4 with high uric acid ,from whom 35 patient were on allopurinol. The patients were attending to the outpatient clinic of the Iraqi Center for Kidney Diseases and Renal Transplantation at the Medical City Teaching Hospital Complex, Baghdad, Iraq. The period of study from June to October 2022. Clinical data were collected and the following investigation were done to all; serum uric, blood urea, serum creatinine and estimated glomerular filtration rate. Results The average of s.uric acid in control group was within normal 6.2 mg/dl , while it was high in CKD patients with allopurinol(6.793mg/dl ) and higher in chronic kidney disease patients without allopurinol (8.240 mg/dl),with significant P value (0.0013). All level of serum uric, blood urea , serum creatinine found to be lower in chronic kidney disease patients who are using allopurinol treatment than in those who are not, with a significant p values
Keywords: allopurinol; uric acid; urea; creatinine